2015
DOI: 10.5604/20828691.1189719
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced cardiotoxicity – two case reports

Abstract: Cisplatin has been used for over 40 years in various cancer chemotherapies. Toxicity induced by cisplatin-based therapeutic regimens include gastrointestinal toxicity, myelotoxicity, neurotoxicity, ototoxicity and nephrotoxicity. Cisplatin-based regimens have been associated with a wide range of cardiovascular complications. In this paper, we report 2 cases of cisplatin-induced cardiotoxicity.We present cases of 2 young patients who developed acute myocardial infarction during combination chemotherapy with ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The clinical use of cisplatin is associated with severe toxicities affecting the cardiac, gastrointestinal, renal, neurological, and hematological systems [ 2 ]. Previous studies have reported multiple cardiotoxic effects of cisplatin such as unstable angina pectoris [ 3 ], bradycardia [ 4 ], acute myocardial infarction [ 5 ], atrioventricular block [ 6 ], and cardiomyopathy [ 7 ]. An increase in oxidative stress and a decrease in antioxidant enzymes are implicated in the cardiotoxic effects of cisplatin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical use of cisplatin is associated with severe toxicities affecting the cardiac, gastrointestinal, renal, neurological, and hematological systems [ 2 ]. Previous studies have reported multiple cardiotoxic effects of cisplatin such as unstable angina pectoris [ 3 ], bradycardia [ 4 ], acute myocardial infarction [ 5 ], atrioventricular block [ 6 ], and cardiomyopathy [ 7 ]. An increase in oxidative stress and a decrease in antioxidant enzymes are implicated in the cardiotoxic effects of cisplatin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing number evidences have revealed that cisplatin produced multiple cardio toxic effects such as unstable angina pectoris [3], cardiac arrhythmias [4], bradycardia [5], acute myocardial infarction [6], hypotension [7], atrioventricular block [8], cardiac failure [9] and cardiomyopathy [10].…”
Section: Introductionmentioning
confidence: 99%